Familial Papular Epidermal Nevus with "Skyline" Basal Cell Layer. Issue 1 (26th November 2013) - Brena, Michela; Besagni, Francesca; Boneschi, Vinicio; Tadini, Gianluca
Abstract Papular epidermal nevus with "skyline" basal cell layer (PENS), a novel keratinocytic nevus, has recently been described as a mosaic condition with varying presentations. We herein describe typical PENS lesions, which usually occur sporadically, affecting two members of the same family. The concept of paradominant inheritance is proposed to explain the paradox of occasional transmission of normally sporadically occurring traits.